Organosulfur-based fullerene materials - Nakahodo, Tsukasa; Ishitsuka, Midori O.; Takano, Yuta; Tsuchiya, Takahiro; Akasaka, Takeshi; Herranz, M. Angeles; Martin, Nazario; Guldi, Dirk Michael; Nagase, Shigeru (Phosphorus Sulfur and Silicon and the Related Elements, 2011)
Chemical functionalizations of an endohedral metallofullerene, La @I-C, and an empty fullerene, C , are demonstrated using organosulfur compounds. A novel donor-acceptor system of La@I-C-exTTF (3) synthesized using the Prato reaction shows photo-induced intramolecular charge separation. On the other hand, the photoreaction of C with N-ptoluenesulfonyl sulfilimine affords N-tosyl-1,2-aziridinofullerene (5). The first reversible interconversion of 1,2-aziridinofullerene and 1,6-azafulleroid was found for mono-substituted fullerenes by thermal rearrangement of 5 to 6. S,S-Diphenylsulfilimines (7) with an electrondonating group on the N atom reacts with C to afford corresponding aziridinofullerenes (8-10) regioselectively. Copyright © Taylor & Francis Group, LLC.